A Numerical Study on the Improvement of the Performance of a Banki Wind Turbine. Issue 1 (February 2014) - Wenlong, Tian; Baowei, Song; Zhaoyong, Mao
Banki wind turbine is a kind of vertical axis wind turbine (VAWT) with high solidity, and has been proved to have a relatively high starting torque and maximum power coefficient under low wind conditions. This study introduces an arc-shaped windshield to further improve the performance of Banki wind turbines. The windshield is placed in front of the turbine to deflect wind and reduce the negative torque on the blades in the upwind direction. Computational investigations are carried out to study the influence of the angle of the arc-shaped windshield on the performance of the turbine using the commercial computational fluid dynamics (CFD) code Fluent 13.0. The results demonstrated that the maximum power coefficient of the Banki wind turbine was increased by 66.9% with the optimal windshield angle of 60°. The maximum power coefficient was found to be 0.2784 at a tip speed ratio of 0.5 in the presence of the windshield.